2016
DOI: 10.12659/pjr.895694
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Mandibular Incisors: A Study on CBCT

Abstract: SummaryBackgroundThe aim of the study was to identify the number of root canals and examine root canal morphology of permanent mandibular incisors in an Indian sub-population of Pune, Maharashtra, India using cone-beam computed tomography (CBCT).Material/MethodsThis study was conducted at Elite CBCT & Dental Diagnostics, Pune. One hundred mandibular incisors were evaluated for the number of root, root canals and root morphology.ResultsIn the present study, amongst 102 mandibular incisors, all had one root, 36%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
2
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 9 publications
1
16
2
3
Order By: Relevance
“…Most of these researches showed that in mandibular incisors the prevalent configuration is Vertucci type I (only one canal), with a percentage ranging from 96,2% to 32,5% (mean value 64,3%). These contradictory data could be explained by the different methodologies adopted (Table 3), since only some studies were conducted with CBCT (35)(36)(37)(38)(39)(40)(41)(42)(43), and very few examined other clinically relevant parameters like confluences (44) and symmetry (45). Theoretically, there should be no significant differences between studies using CBCT or extracted teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these researches showed that in mandibular incisors the prevalent configuration is Vertucci type I (only one canal), with a percentage ranging from 96,2% to 32,5% (mean value 64,3%). These contradictory data could be explained by the different methodologies adopted (Table 3), since only some studies were conducted with CBCT (35)(36)(37)(38)(39)(40)(41)(42)(43), and very few examined other clinically relevant parameters like confluences (44) and symmetry (45). Theoretically, there should be no significant differences between studies using CBCT or extracted teeth.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies revealed high variation of root canal morphology among mandibular anterior teeth. 8,9 Mandibular canines, similar to mandibular incisors, have a root wider bucco-lingually than mesio-distally. Many studies reported that these teeth infrequently have two or more roots or canals.…”
Section: Cone Beam Computed Tomography (Cbct)mentioning
confidence: 99%
“…Many studies reported that these teeth infrequently have two or more roots or canals. 9,10 Several studies have investigated root canal morphology using various diagnostic methods. 11,12 These methods include polyester resin impressions, creating transparent samples and taking radiographs in the mesiodistal and/or buccolingual directions.…”
Section: Cone Beam Computed Tomography (Cbct)mentioning
confidence: 99%
“…They found that Vertucci type I and type III configurations were more prevalent in both mandibular central and lateral incisors [19]. 81.37% of teeth had a single canal and 28.43% of teeth had two canals, Type 1 Vertucci configuration was found to be the most prevalent one, and type 4 the least prevalent in the study conducted by Kamtane & Ghodke on the mandibular incisors of Indian sub population of Pune [20].…”
Section: Discussionmentioning
confidence: 99%